THE LEARNING OF REMAINDER THEOREM CONCEPT ON POLYNOMIAL DIVISIONWITH THE DIVISOR OF AX-B - Ali, Sukarni
This study aims to describe students understanding about the concept of remainder theorem through the theorem proving approach. A Learning design called understanding by design template is used in the approach. This qualitative study was conducted at the level XII grade in Bandung. The diagnostic test results show that the students have not been able to explain, to apply and to prove the concept of the remainder theorem.Through the learning of remainder theorem on polynomial disivision with the divisor of a-b , the knowledge of the observed students in explaining, applying and proving the concept of the remainder theorem is improved.